Kebijakan Upah Minimum yang Akomodatif - - Suparjan; Hempri Suyatna (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
In attempting to mediate conflict of interest between labours and enterprises, the government set up a regional-base minimum wage. Such policy, however suffer from some flows. Having demonstrate the flows, this article offers some measures to improve it.